Microstructure and electrical properties of 0-3 connectivity barium titanate−Portland cement composite with 40% barium titanate content - Rianyoi R. (2017)
© 2016 Taylor and Francis Group, LLC. In this paper, a study is presented on the microstructure, dielectric and piezoelectric properties of 0–3 connectivity barium titanate-Portland cement composite with 40% barium titanate content at this composition has an acoustic impedance that match with concrete structure. The results show that both of dielectric constant (ε r ) and dielectric loss (tanδ) of composite were found to decrease with increasing frequency. The ε r value of composite was 239 at a frequency of 1 kHz. In addition, the ferroelectric hysteresis loops of composite indicate that the “apparent” remnant polarization increases as an applied external electrical field increases. Furthermore, the piezoelectric coefficient was 7 pC/N under a low poling field of 1 kV/mm.